2021
DOI: 10.21037/atm-21-3242
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up study of loose combined cutting seton surgery for patients with high anal fistula

Abstract: Background: The treatment of high anal fistula (HAF) is still difficult for clinical surgeons. Our previous study demonstrated the short-term benefit of loose combined cutting seton (LCCS) for patients with HAF.This study aimed to evaluate the long-term effectiveness of LCCS for treating HAF patients.Methods: We retrospectively enrolled consecutive HAF patients who received LCCS therapy in our hospital between March 2014 and July 2017. After enrollment, all patients were followed up by clinical review. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(33 reference statements)
0
5
0
1
Order By: Relevance
“…Fistula relapse was also observed in only two patients (4.8%) 30 . According to Zhi et al, 31 22 subjects (18 males, four females) were examined for a mean of 3.65 years after receiving loosely combined cutting seton (LCCS). All patients were cured, and there were no recurrences during the follow‐up period, highlighting the effectiveness, safety, and reliability of LCCS in treating patients with high anal fistulas 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fistula relapse was also observed in only two patients (4.8%) 30 . According to Zhi et al, 31 22 subjects (18 males, four females) were examined for a mean of 3.65 years after receiving loosely combined cutting seton (LCCS). All patients were cured, and there were no recurrences during the follow‐up period, highlighting the effectiveness, safety, and reliability of LCCS in treating patients with high anal fistulas 31 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Zhi et al, 31 22 subjects (18 males, four females) were examined for a mean of 3.65 years after receiving loosely combined cutting seton (LCCS). All patients were cured, and there were no recurrences during the follow‐up period, highlighting the effectiveness, safety, and reliability of LCCS in treating patients with high anal fistulas 31 . Omar et al 32 implemented a prospective randomized controlled trial to compare the clinical outcomes between the separate drainage seton and drainage seton combined with fistula tract rerouting (EAS‐sparing Seton after rerouting).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the loose seton technique can improve drainage and accelerate the stages of healing without a high risk of injury to the sphincter. Although the cutting seton can totally cure the fistula by gradually transecting the external sphincter muscle, it often results in some complications, including incontinence and even severe post-operative pain [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Short-and long-term benefits have been observed with the use of loose setons. 7 It has been reported that loose seton use is beneficial in patients with transsphincteric anal fistulas. The preservation of an anatomical loss of the external sphincter function is important with this technique.…”
Section: Introductionmentioning
confidence: 99%